Level of Cybercrime Threat During the Outbreak of COVID-19 Pandemic : A Study in Malaysia - Tharshini, N. K.; Faizah, Haji Masud; Zamri, Hassan (Human Resource Management Academic Research Society, 2022)
Cybercrime threat has shown a sudden increase during the enforced stay-at-home order due to the outbreak of the COVID-19 pandemic. Thus, empirical research was conducted in providing substantial evidence regarding the level of cybercrime threats in Malaysia during the outbreak of the COVID-19 pandemic. A quantitative approach was used to collect data among 332 respondents across Malaysia. The finding stipulated that a large number of respondents have experienced a high level of online phishing/malware distribution (72.9%), a moderate level of online fraud (69.2%), and a moderate level of online sexual harassment (87.7%). The move to explore the level of cybercrime threat experienced by the public during the outbreak of the COVID-19 pandemic is essential to detect, disrupt, and mitigate cybercrime threats during unprecedented situations.